An unusual variant of the sphenopalatine foramen and artery with an absent crista ethmoidalis: an intra-operative challenge - Loo, LY; Fahrin Zara Nasseri, (Pusat Perubatan Universiti Kebangsaan Malaysia, 2017)
Sphenopalatine artery ligation (SPL) is a surgical remedy for severe epistaxis. This procedure requires extensive knowledge of the various anatomical variants. Its topographical anatomy varies and reliable landmark such as the crista ethmoidalis may be absent. These variations are crucial and they dictate the outcome of the surgery. We present a peculiar case of a postero-superiorly located variant of the sphenopalatine foramen and artery with an absent crista ethmoidalis. The sphenopalatine foramen was found superiorly at the superior meatus beyond the horizontal part of the lamella of the superior concha. Only one trunk was seen exiting the sphenopalatine foramen. The sphenopalatine foramen was measured from the anterior part of the nose. It was 69mm from the nasal sill and 54mm limen nasi.